The colors of the empire: Assessing techno-decorative innovations in local, hybrid and intrusive ceramic pigments within the Wari interaction spheres, Peru - Muro Ynoñán, L.A.; Nash, D.; Gorman, A.; Vaughn, K.J.; del Solar Velarde, N.; Banikazemi, C.; Witte, E.; Edwards, M. (Elsevier, 2023)
Ancient empires developed diverse strategies of political and cultural domination in their conquered territories. One such strategy involved introducing imperially branded goods that reinforced a legitimizing ideology. The appearance of intrusive styles may be an indicator of political dominance; however, the introduction of new technologies is a stronger indicator of interpersonal engagement between people in the empire’s core and dominated regions. In this paper, we specifically focus on innovations in colors, pigments, and decoration of intrusive, local, and hybrid ceramic styles resulting from the interaction between the Wari Empire (600–1050 CE) of the Central Andes and local societies from the north and south coast of Peru. These innovations can be documented long after the Wari influence faded in each region. By integrating archaeological and archaeometric perspectives, we examine techno-decorative innovations among locally produced pottery within the imperial interaction spheres. This paper presents and compares the results of chemical and mineral analyses conducted on samples of pigments on decorated ceramics from the Valleys of Jequetepeque, Nasca, and Moquegua. Results indicate that Wari could have directly promoted the circulation of specific ceramic pigments that guaranteed a particular “Wari experience of color.” We argue that an inter-site approach to the study of colors, pigments, and decoration can better contribute to the understanding of politics and ceramic production relationships, religious syncretism, and cultural change in the Andean past.
Keywords: Andean Archaeology; Wari Empire; https://purl.org/pe-repo/ocde/ford#6.03.00